Творча спадщина українського етнографа і фольклориста Марка Грушевського - Кукса, Н. (Матеріали до української етнології, 2013)
У статті подано стислий огляд збирацько-дослідницького доробку українського етнографа і фольклориста М. Грушевського. Ім’я подвижника етнографічної науки, яке впродовж десятиліть було незаслужено забуте, у роки незалежності України широко популяризують. Творчий доробок М. Грушевського набуває практичного використання. В статье подан краткий обзор исследовательского наследия украинского этнографа и фольклориста М. Грушевского. Имя подвижника этнографической науки, которое на протяжении долгих десятилетий было незаслуженно забыто, в годы независимости Украины широко популяризируется. Творческое наследие М. Грушевского приобретает практическое использование. The article gives a brief review of the collecting and research work of Ukrainian ethnographer and folklorist Marko Hrushevskyi. The name of this devotee of ethnographic science, which has been undeservedly forgotten for many decades, has been widely popularized through the years of Ukrainian independence, particularly, some of his collections were partially reprinted. According to descriptions of the anthropologist, there have been reconstructed the traditional folk dolls. The Museum of Child, the first in Ukraine, was founded in Subotiv. The creative work of Marko Hrushevskyi now acquires a practical use.